2018
DOI: 10.25251/skin.2.2.3
|View full text |Cite
|
Sign up to set email alerts
|

Prospective, Multicenter Clinical Impact Evaluation of a 31-Gene Expression Profile Test for Management of Melanoma Patients

Abstract: Objective: A 31-gene expression profile (GEP) test that has been clinically validated identifies melanoma patients with low (Class 1) or high (Class 2) risk of metastasis based on primary tumor biology.  This study aimed to prospectively evaluate the test impact on clinical management of melanoma patients.Methods:  Physicians at 16 dermatology, surgical or medical oncology centers examined patients to assess clinical features of the primary melanoma.  Recommendations for clinical follow-up and surveillance wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
31
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 11 publications
3
31
0
Order By: Relevance
“…15 Subsequent studies have analysed the use of the 31-GEP test in combination with the AJCC stage system and found that this approach improves the identification of patients at risk of relapse. 18,19 In this report, we also combined GEP with the AJCC score confirming that patients with higher AJCC (IIB-IIC) staging and Class 2 GEP are at a greater risk of relapse. Nevertheless, two patients with a low-risk AJCC stage and a Class 2 GEP metastasized.…”
Section: Discussionsupporting
confidence: 58%
See 2 more Smart Citations
“…15 Subsequent studies have analysed the use of the 31-GEP test in combination with the AJCC stage system and found that this approach improves the identification of patients at risk of relapse. 18,19 In this report, we also combined GEP with the AJCC score confirming that patients with higher AJCC (IIB-IIC) staging and Class 2 GEP are at a greater risk of relapse. Nevertheless, two patients with a low-risk AJCC stage and a Class 2 GEP metastasized.…”
Section: Discussionsupporting
confidence: 58%
“…14 Recently, new prognostic tests based on genetic profiling signatures have been developed to better identify those patients who are at a higher risk of developing metastasis leading to death. [15][16][17][18][19][20] A gene expression profile (GEP) test (DecisionDx-Melanoma, Castle Biosciences, Inc., Friendswood, TX, USA) evaluates 31 genes of primary cutaneous melanoma tumours and based on the expression of these genes (genetic signature) it classifies patients into two groups of risk of relapse, low (class 1) or high (class 2). This test has been validated in several historical cohorts showing that its prognostic ability is independent from the clinical and pathological features of the tumour.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a 31-GEP class 1 result provides reassurance of a low-risk tumor, leading to reduced intensity of patient follow-up and referral patterns. [3][4][5] One could argue that patients who have a negative sentinel lymph node biopsy result but experience metastasis are also harmed by an incorrect result; notably, these patients constitute the majority of those who die of melanoma. 6 In their model for 31-GEP clinical value based on test accuracy metrics, Marchetti et al 2 have not only overestimated the incidence of a class 2 result in T1 tumors but have also failed to account for the 31-GEP subclasses 1A (lowest risk), 1B, 2A, and 2B (highest risk).…”
mentioning
confidence: 99%
“…Distinguishing class 1A tumors with a higher than 95% negative predictive value (99% in Greenhaw et al 3 ) and class 2B tumors with a 40% positive predictive value for recurrence is impactful for patients. 4,5 Clinicopathologic features do not identify all thin melanomas that will recur. The multivariate analysis described in Gastman et al 7 ( Supplementary Table III [available at http://www.jaad.org]) emphasizes the value of molecular subclassification in the context of these factors; the 31-GEP class 2B result was the only feature independently associated with recurrence risk for T1 tumors.…”
mentioning
confidence: 99%